miR-27b Suppresses Tongue Squamous Cell Carcinoma Epithelial–Mesenchymal Transition by Targeting ITGA5 - Li, Tao (Onco Targets Ther, 2020)
BACKGROUND: MicroRNA27b-3p (miR-27b) has been reported to be dysregulated in multiple types of human cancer. However, the expression levels, biological roles, and underlying mechanism of miR-27b in tongue squamous cell carcinoma (TSCC) remain to be elucidated. METHODS: Bioinformatics analyses and quantitative real-time PCR (qRT-PCR) were used to determine miR-27b expression in TSCC tissues and cell lines. The influence of miR-27b overexpression or inhibition on TSCC cell proliferation, migration, and invasion in vitro, and on tumor growth in vivo, was explored via CCK8, colony formation, wound healing, and transwell assays, and in xenograft tumors in nude mice, respectively. Luciferase reporter assays, qRT-PCR, and Western blotting were performed to clarify the potential mechanisms involving miR-27b in TSCC cells. RESULTS: miR-27b was significantly downregulated in TSCC tissues and cell lines, and its expression was correlated with cancer status. Overexpression of miR-27b led to diminished proliferation, migration, and invasion, and notably reduced tumor growth in vivo. Bioinformatics analysis followed by luciferase reporter assays demonstrated that miR-27b expression was inversely correlated with that of integrin subunit α5 (ITGA5)and that miR-27b directly bound to the 3ʹ-untranslated region of ITGA5 in TSCC cells. The bioinformatics analysis also indicated that ITGA5 was upregulated in TSCC and that its expression was correlated with epithelial–mesenchymal transition (EMT) and poor prognosis. Moreover, we found that miRNA-27b could reverse ITGA5-induced promotion of TSCC cell proliferation and migration. Finally, we demonstrated that regulation of miR-27b expression in TSCC may result in alterations in the expression of ITGA5 and EMT-related marker genes at the mRNA and protein levels. CONCLUSION: These results indicate that miR-27b hampers TSCC proliferation and migration via suppressing the EMT process by targeting ITGA5. These findings support consideration of miR-27b/ITGA5 as a valuable marker for the metastatic potential of TSCC, or as a therapeutic target for the treatment of TSCC.